Social Contacts, Dutch Language Proficiency and Immigrant Economic Performance in the Netherlands: A Longitudinal Study - Barry R. Chiswick; Zhiling Wang (Institute for the Study of Labor (IZA), 2016)
Using longitudinal data on immigrants in the Netherlands for the years 1991, 1994, 1998, 2002, we examined the impacts of social contacts and Dutch language proficiency on adult foreign-born men's earnings, employment and occupational status. The main conclusions are as follows. On average, social contacts and a good mastery of the Dutch language enhance immigrants' economic performances. The effects are stronger for immigrants with low-skill-transferability than for immigrants with high-skill-transferability, and are stronger for economic migrants than for non-economic migrants. Contact with Dutch people and Dutch organisations unambiguously enhances all aspects of immigrants' economic performance, however, we found no evidence for the positive effect of co-ethnic contact on employment status.
Keywords: J15; J61; Z13; 330; social capital; Dutch language proficiency; labour market performance; Dutch immigrants; skill transferability